Geodatabase per la valutazione speditiva a larga scala della vulnerabilità sismica di un’area urbana complessa: applicazione alla città di Firenze - Pauline Deguy; Maurizio Ripepe; Giorgio Lacanna; Letizia Orti (Bollettino della Società Geografica Italiana)
The seismic vulnerability assessment of a city is usually based on buildings’ characteristics, underground geophysical properties, socio-economic activities, and population density. This research highlights the value of a complete and manageable database for large-scale seismic vulnerability assessment of urban areas: such databases are often missing or partially developed for the majority of Italian cities. This study is based on the creation of a GIS database containing useful information to identify and valuate some indicators of seismic vulnerability in order to understand an earthquake’s effect for the actual configuration of a city. This system could be a growing source of information on cities and, if used in the proper way, a useful tool for monitoring, for seismic vulnerability assessment, and for spatial urban planning. The experience gained in this field of application can be transferred to other situations, both for the procedures and the workflow system.